Thermoplastic starch foamed composites reinforced with cellulose nanofibers: Thermal and mechanical properties. (1st October 2018) - Ghanbari, Abbas; Tabarsa, Taghi; Ashori, Alireza; Shakeri, Alireza; Mashkour, Mahdi
Highlights: TPS and TPS/CNFs foamed films were prepared using extrusion process. Thermo-mechanical properties of TPS were enhanced after addition of CNFs. TGA and DSC results showed that addition of CNFs can improve thermal stability. SEM images showed CNFs dispersion within the matrix was uniform with smooth surface. Abstract: The present work reports the effect of cellulose nanofibers (CNFs) on the thermal, dynamic mechanical analysis (DMA), density and water uptake of thermoplastic starch (TPS) foamed composites. The obtained thermal and DMA results illustrate that thermal stability, storage modulus ( E′ ), loss modulus ( E″ ) and damping factor (tan δ) increase for all TPS/CNF samples compared to the pure TPS foamed composite. The results showed that the incorporation of CNFs caused an increase in the glass transition temperature (Tg ) of the TPS foamed composites. Additionally, thermal results revealed that 1.5 wt% CNF offers superior resistance or stability towards heat compared to its counterparts. Addition of the CNF filler into the TPS matrix decreased the apparent density and water absorption. Interestingly, SEM images illustrate that when a small content of rigid nano particles (1.0 or 1.5 wt%) was added in the foamed composites, the cell size decreased while the cell density increased.